Caracterização de resíduos recicláveis: estudo de caso na coleta seletiva do município de Caçapava do Sul-RS - Oliveira, Stener Camargo de (2016)
Urban solid wastes are those that originate from domestic and commercial activities as well as those originating from urban sanitation services, which when disposed of in undue places lead to a series of environmental and public health problems. In 2010, after 20 years of discussions, the Brazilian National Congress passed Law 12,305, which establishes the National Solid Waste Policy, based on the concept of shared responsibility, society as a whole became responsible for the environmentally sound management of waste Solids. This work intends to identify the neighborhoods with the highest generation of recyclable residues through research with the population, as well as to perform the gravimetric classification of these through the quarteamento method. It can be seen that there is a lack of incentive on the part of the Municipal Public Power for the Selective Collection of Caçapava of the South, since there are no campaigns of sensitization and divulgation of the script of this Collection.